Electroacupuncture exerts neuroprotective effects and alters gut microbiota in a MPTP-induced mouse model of Parkinson’s disease - Wu, Xi-Chen; Dong, Yi-Yue; Ying, Yu-Chen; Chen, Guang-Yan; Wang, Xi; Fan, Qian; Yin, Ping; Chen, Yue-Lai (Frontiers in Neuroscience, 2026)
ObjectiveTo investigate the therapeutic mechanism of electroacupuncture (EA) in a mouse model of Parkinson’s disease (PD) induced by 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP).MethodsMotor functions were evaluated using open field test and pole tests. Tyrosine hydroxylase (TH) expression in the substantia nigra and striatum was detected by immunohistochemistry. Intestinal barrier integrity was assessed via immunofluorescence staining of tight junction proteins ZO-1 and Occludin. Gut microbiota composition was analyzed by 16S rRNA sequencing.ResultsEA treatment significantly improved motor deficits, restored TH expression in nigrostriatal regions, and enhanced colonic ZO-1 and Occludin levels. EA reversed MPTP-induced dysbiosis, notably normalizing the abundances of Dubosiella, Lactobacillus, Enterococcus, Desulfovibrio, Bacteroides, Allobaculum, and Parasutterella. Microbial co-occurrence network analysis revealed that EA simplified hyperconnected interactions and improved network stability.ConclusionEA treatment attenuated PD progression, which was associated with the remodeling of gut microbiota structure and restoration of microbial network stability. The concomitant protection of dopaminergic function suggests a potential link mediated by the gut–brain axis.